Camp David : peacemaking and politics - Quandt, William B. (Washington, D.C. : Brookings Institution, 1986)
In September 1978, William Quandt, a member of the White House National Security Council staff, spent thirteen days at Camp David, where Jimmy Carter, Anwar Sadat, and Menachem Begin were holding secret negotiations. Quandt's book is not only an eyewitness account but a scholar's reconstruction of the event, with insights into the people, politics, and policies.
Map on lining papers.
Includes index.
Includes bibliographical references: p. 413-414.
aia 18/05/2018
Loans
Keywords: Israel-Arab War, 1973- Peace; Egypt, Treaties; Foreign relations- United States; United States; Middle East